The physical origin and the properties of arm spurs/feathers in local simulations of the wiggle instability - Mandowara, Yash; Sormani, Mattia C.; Sobacchi, Emanuele; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2022)
Gaseous substructures such as feathers and spurs dot the landscape of spiral arms in disc galaxies. One of the candidates to explain their formation is the wiggle instability of galactic spiral shocks. We study the wiggle instability using local 2D hydrodynamical isothermal non-self-gravitating simulations. We find that: (1) simulations agree with analytic linear stability analysis only under stringent conditions. They display surprisingly strong non-linear coupling between the different modes, even for small mode amplitudes (${\sim}1{{\ \rm per\ cent}}$). (2) We demonstrate that the wiggle instability originates from a combination of two physically distinct mechanisms: the first is the Kelvin-Helmholtz instability, and the second is the amplification of infinitesimal perturbations from repeated shock passages. These two mechanisms can operate simultaneously, and which mechanism dominates depends on the underlying parameters. (3) We explore the parameter space and study the properties of spurs/feathers generated by the wiggle instability. The wiggle instability is highly sensitive to the underlying parameters. The feather separation decreases, and the growth rate increases, with decreasing sound speed, increasing potential strength and decreasing interarm distance. (4) We compare our simulations with a sample of 20 galaxies in the HST Archival Survey of Spiral Arm Substructure of La Vigne et al. and find that the wiggle instability is able to reproduce the typical range of feather separations seen in observations. It remains unclear how the wiggle instability relates to competing mechanisms for spur/feather formation such as the magneto-jeans instability and the stochastic accumulation of gas due to correlated supernova feedback.
Gesehen am 29.06.2022